Identifikasi Lapisan Akuifer Berdasarkan Survei Geolistrik Konfigurasi Schlumberger di Desa Botumoputi, Kabupaten Gorontalo - Aril A.H Sahidah; Ahmad Zainuri; Noviar Akase (Journal of Applied Geoscience and Engineering, 2025)
A continuously growing population day by day means that the need for water is also increasing.The majority of the Botumoputi Village community uses groundwater every day through dug wells and drilled wells for their daily needs. The purpose of the study was to determine the subsurface geological conditions that can be used as a reference in estimating the location, thickness, depth and type of aquifer. The method used is the resistivity geoelectric method using the Schlumberger configuration. Measurements were carried out at 3 points with a span length of 300 m each. Data processing and interpretation using software IPI2win. The results of processing Schlumberger configuration geoelectric data and subsurface geological interpretation to identify the type of groundwater aquifer in the Botumoputi area show 3 layers of rock types based on their resistivity values, namely top soil, clay and sand. It is estimated that the potential for groundwater is found in TS1 and TS2 where the lithology that acts as an aquifer is sandstone with a resistivity value of 16.8 - 42.7 ohms with a depth ranging from 3.93 - 17.2 m with a thickness of 8.88 - 13.27 m and is interpreted as a shallow aquifer.